Functional characterization of a JAG1 5'UTR variant in a patient with clinically observed Alagille syndrome. Issue 3 (27th June 2022) - Buhl, Nicole; Pfister, Eva‐Doreen; Bohne, Jens; Baumann, Ulrich; Hartleben, Björn; Schlegelberger, Brigitte; Illig, Thomas; Skawran, Britta; Stalke, Amelie
Abstract :